Steder og ikke-steder - “Telefonen” i Walter Benjamins Barndom i Berlin omkring år 1900 - Schlosser, Jan T. (Passage - Tidsskrift for litteratur og kritik, 2014)
Jan T. Schlosser: “Places and Non-Places: “The Telephone” in Walter Benjamin’s Berlin Childhood around 1900” Drawing on the French anthropologist Marc Augé’s theory of ‘places’ and ‘non-places’, the article analyses Walter Benjamin’s text “The Telephone” and other texts from Berlin Childhood around 1900. The analysis argues that Benjamin’s “The Telephone” establishes a tension between places and non-places and signals the transition from modernity to the period that Augé labels supermodernity.